“Let’s turn to the first page”: the page as stage in contemporary British drama - Rousseau, Aloysia (Status Quaestionis, 2022)
By looking at a number of contemporary British plays, this paper wonders whether the play script can be deemed a self-sufficient entity rather than a frustrating first step towards a much more fulfilling theatrical experience. Are plays to be read only when we are deprived of their transposition to the stage – as in times of pandemic crisis – or is the act of reading a play a satisfying experience per se? Focusing on Tim Crouch’s plays, the second part of the essay will throw light on the emphasis placed on the script and on the figure of the reader in his work before suggesting that the theatrical experience in fact sublimates the act of reading.